2004
DOI: 10.1016/j.immuni.2004.09.012
|View full text |Cite
|
Sign up to set email alerts
|

SAP Regulates TH2 Differentiation and PKC-θ-Mediated Activation of NF-κB1

Abstract: XLP is caused by mutations affecting SAP, an adaptor that recruits Fyn to SLAM family receptors. SAP-deficient mice recapitulate features of XLP, including increased T cell activation and decreased humoral responses post-infection. SAP-deficient T cells also show increased TCR-induced IFN-gamma and decreased T(H)2 cytokine production. We demonstrate that the defect in IL-4 secretion in SAP-deficient T cells is independent of increased IFN-gamma production. SAP-deficient cells respond normally to polarizing cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
281
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(301 citation statements)
references
References 44 publications
18
281
2
Order By: Relevance
“…Similar modifications resulting in substantial m.w. shifts have also been observed by others (16,18,31,32).…”
Section: Bcl10 Is Phosphorylated On Ser 138 In Activated T Cellssupporting
confidence: 80%
“…Similar modifications resulting in substantial m.w. shifts have also been observed by others (16,18,31,32).…”
Section: Bcl10 Is Phosphorylated On Ser 138 In Activated T Cellssupporting
confidence: 80%
“…SAP seems to be important for the modulation of TCR signals, leading to the initiation of apoptotic pathways. Cannon's study showed that SAP is recruited to the immune synapse upon TCR stimulation in WT CD4 + T cells, suggesting that SLAM family receptors can fine-tune the TCR signals [16]. Thus, SAP deficiency causes reduced apoptosis in CD8 + T cells, instead of switching off the entire apoptotic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well established that SAP is an essential adaptor due to its capacity to recruit FynT to SLAM and p85 of PI3 K to 2B4, respectively [9,10]. SAP is expressed in activated T, NK and NKT cells, as well as in germinal center B cells [11,12], and is indispensable for normal NKT cell development, generation of a proper Th2 response and Ig class switching in humans and mice [13][14][15][16][17][18]. In XLP patients, both EBV-infected B cells and EBVspecific CTL hyper-proliferate, although the underlying mechanism is still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…GATA-3 is up-regulated in response to IL-4/STAT-6 and TCRinduced signals (4,24). It seemed feasible that a block in GATA-3 expression could underlie the failure of CD4 T cells to commit to the Th2 lineage.…”
Section: Neither Up-regulation Of T-bet Expression Nor Early Suppressmentioning
confidence: 99%